Musical Instruments and Singing in Abbasid Poetry: A Cultural Exploration - Al-Dahoun, Ibrahim Mustafa Muhammad (Dirasat: Human and Social Sciences, 2025)
Objectives: This research aims to examine the use of musical instruments in Abbasid poetry, specifically through examples of singing gatherings. These gatherings evoke vivid images of Abbasid social and cultural life, characterized by joy, pleasure, elegance, and radiance, reflecting the pleasures and vibrancy of earthly life. Methodology: The researcher adopted a cultural approach to reflect significant aspects of Arab social life in the Abbasid era, which are embodied in the imagination, beauty, and ecstasy found in music and singing. The study is organized into an introduction, two sections, and a conclusion. The first section covers the names of musical instruments and singing gatherings in Abbasid poetry. The second section explores the semantic codes and cultural implications of the instruments used in Abbasid singing councils. Results: The study reveals that musical instruments highlighted various social classes within Abbasid society. There was notable variation among Abbasid poets in their use and acceptance of these musical instruments. Conclusion: The study concludes that the Abbasid poets, through their engagement with musical spaces and rituals, exhibited a presence that indicated a desire to escape the social and cultural oppression and the harsh institutional frameworks of their time. The discussion of musical instruments began as a common social phenomenon and evolved into a significant cultural pattern integral to Abbasid life.